MEWUJUDKAN WORLD CLASS PROFESSIONALISM OF LIBRARIANS DI ERA LIBRARY MOBILE - Yuni Nurjanah (Jurnal Pustaka Ilmiah, 2019)
At the century, library has offered exceptional service via mobile web users. This concept refers to the components of the mobile web - Ellyssa Kroski: users, devices, operating systems, services, content. The device not only machines, including human resources (librarian). Course professional librarians, brave move on, becoming a greater. It leads to the aspect of librarian professionalism - Steers & Porter (1991) that professional librarians are not different from other professions. Its benchmarks 1) the skills, abilities, and knowledge; 2) psychological maturity. The professionalism of thiscentury was also characterized by a global culture which is full of competition and fast-paced change. Not just the usual professionalism, but world-class professionalism that will enable us to dominate the Mobile Library and align us with other professional organizations worldwide. These has become the premise to realize a world class professionalism of librarians in the era of the mobile library. How to? These will be discussed in this article.Keywords: mobile web, web libraries, professional librarian